PROBLEMS AND COUNTERMEASURES ON APPLYING THE TRANSFORMATIVE LEARNING THEORY TO CHINA’S COLLEGE ENGLISH TEACHING - Jiaquan Wang; Wendy Hiew; Suyansah Swanto (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The literature review resources on applying Transformative Learning Theory (TLT) in China’s college English teaching are very scarce. This paper aims to contribute to more literature in the field English teaching in college. The study adopted a qualitative design and utilized open-ended interview with eight college English teachers in China. The participants were purposefully selected. Findings from the interview showed that most of the college English teachers did not know about TLT and the measuring method of the transformative learning. The complexity of the TLT and teachers’ paradigm prevented the teachers from using TLT in their college English teaching. The difficulty of altering the student’s perspectives and beliefs was also obvious. Therefore, the present researchers proposed five countermeasures to apply TLT in China’s college English teaching and learning: i) introducing more works of the TLT and measuring methods, ii) building up inter-disciplinary research groups to explore the application of TLT, iii) introducing and exploring the measuring methods of transformative learning, iv) exploring the use of the TLT to solve practical teaching problems, and v) developing open-minded attitudes towards research methods. If college English teachers and administrators of the higher education can be enlightened with the these suggestions, it is hoped there will be more application of the TLT in China’s college English teaching in the future.